Odpowiedzi

Najlepsza Odpowiedź!
2009-12-09T20:44:19+01:00
A) 0,3x= -0,4 / * 10
3x = -4 /:3
x = -4/3

b) x+2-(2x-1)=2
x+2 - 2x + 1 = 2
- x + 3 = 2
x = 1

c) 3:(1-5x)=2:(4x-3)
3*(4x-3) = 2*(1-5x)
12x - 9 = 2 - 10x
12x + 10x = 11
22x = 11
x = 0,5

d) -5x+4>-3x-10

-5x + 3x = -10 - 4
-2x > - 14
x < 7

e) 5-3(x-6) ≥ 2+5x

5 - 3x + 18 ≥ 2 + 5x
23 ≥ 2 + 8x
21 ≥ 8x
x ≤ 2 ⅝

f) 3x:5 -10:(x+4≥0
g) -3(x+4)+5< 2(x-6)

tych juz mi sie nie chce robic :P
1 5 1
2009-12-09T20:46:48+01:00
<a. 0,3x= -0,4 x= -4/3
b. x+2-(2x-1)=2
x+2-2x+1=2
-x=2-2-1
-x=-1/:(-1)
x=1
c. 3:(1-5x)=2:(4x-3)/×6
2-10x=12x-9
-10x-12x=-9-2
-22x=-11
x=0,5
d.-5x+4>-3x-10
-5x+3x>-10-4
-2x>-14/:(-2)
x<7
e. 5-3(x-6)≥ 2+5x
5-3x+18≥2+5x
-3x-5x≥2-18-5
-8x≥-21
x≤2 5/8
g. -3(x+4)+5<2(x-6)
-3x-12+5<2x-12
-3x-2x<-12+12-5
-5x<-5/:-5
x>1
2009-12-09T20:48:41+01:00
A) 0,3x= -0,4|: 0,3
x=-1 1/3

b) x+2-(2x-1)=2
x+2-2x+1=2
-x=-1|: (-1)
x=1

c) 3:(1-5x)=2:(4x-3)
d) -5x+4>-3x-10
-5x+3x>-10-4
-2x>-14|: (-2)
x<7
e) 5-3(x-6)≥2+5x
5-3x+18>/ 2+5x
-3x-5x>/2-5-18
-8x>/ -21|: (-8)
x<\ 2 5/8
f) 3x:5 -10:(x+4≥0
g) -3(x+4)+5< 2(x-6)
-3x-12+5<2x-12
-3x-2x<-12+12-5
-5x<5|: (-5)
x>1